The Witness as Object Video Testimonies in Holocaust Museums - de Jong, Steffi (Museums & Collections, 2018)
Today more than ever before, the historical witness is now a "museum object" in the form of video interviews with individuals remembering events of historical importance. Such video testimonies now not only are part of the collections and research activities of museums, but become deeply intertwined with narrative and exhibit design. With a focus on Holocaust museums, this study scrutinizes for the first time this new global process of "musealisation" of testimony, exploring the processes, prerequisites, and consequences of the transformation of video testimonies into exhibits.